Botryosphaeriaceae associated with diseases of mango (Mangifera indica) - T. Trakunyingcharoen (2018)
Fungal species of Botryosphaeriaceae have a cosmopolitan distribution and are important pathogens of a wide range of plant hosts. This study aims to use phylogenetic inference to review the geographical distribution of botryosphaeriacous species that have been associated with diseases of mango (Mangifera indica) globally. The phylogenetic analyses were performed based on the combined sequence datasets of the internal transcribed spacer (ITS) region of the nuclear rDNA and a partial region of the translation elongation factor 1-alpha (EF1-α) gene. The phylogenetic study revealed seven clades with distinct morphological characters from several countries, including Australia, Brazil, Egypt, Iran, Mali, Peru, South Africa, Taiwan and Thailand. Lasiodiplodia theobromae appears to be a dominant species on mango with the largest geographical distribution, whereas L. crassispora and Barriopsis iraniana have only been reported on mango in Brazil and Iran, respectively. These finding indicate that most of the species reported from mango are not restricted to specific geographical regions, although some genera appear to have a limited distribution. © 2014 Australasian Plant Pathology Society Inc.